SOME CHARACTERISTICS OF LIPIDS AND LIPOPROTEINIES METABOLISM IN SYRIAN HAMSTERS FEMALES OF DIFFERENT AGE UNDER THE EXPERIMENTAL METABOLIC SYNDROME - Загайко, А.Л.; Брюханова, Т.О.; Шкапо, А.І. (World of Medicine and Biology, 2015)
The purpose of this paper was to investigate age peculiarities of lipids and lipoproteins metabolism in liver homogenate and blood serum of female Syrian golden hamsters’ age 4 and 20 weeks affected by experimental metabolic syndrome that was simulated by keeping animals on high-calorie diet. Materials and methods. Females of Syrian golden hamsters were used as the experimental animals age of 4 weeks, 20 weeks and 1 year. Metabolic syndrome was simulated by keeping animals on rich source of energy (preferably saturated lipids) and fructose diet. The object of research was liver homogenate and hamsters’ blood serum. Animals were divided into 2 experimental groups: intact control (healthy animals) and animals with metabolic syndrome (MS) – female hamsters kept on high-calorie diet during 5 weeks. The following parameters were studied in blood serum: free fatty acids content, triacylgliceroles, activity of liver triglyceridlipase, estradiol content. Concentration of general lipids in liver homogenate and activity of glucose-6-phosphate-dehydrogenase was determined. Lisosomal lipase activity in lisosomal-mitochondrial fraction of liver. Rate of cholesterol esterification and cholesterol ethers transportation was estimated in the isolated fractions of high-density lipoproteins by centrifugation. Free cholesterol and esterified cholesterol content in the composition of high-density lipoproteins. The content of high-density lipoproteins and Apo-B-containing lipoproteins in blood serum and liver homogenate was determined.
Keywords: metabolic syndrome; metabolism of lipids and lipoproteins; age-related changes